2020
DOI: 10.1080/13670050.2020.1781780
|View full text |Cite
|
Sign up to set email alerts
|

Speech and language outcomes in low-SES Spanish-English bilingual preschoolers: the role of maternal education

Abstract: children. Her current research investigates the relation between technology use, school belonging, and academic performance among first generation college students and the relation between parents' and children's home media use and children's sleep, behavior problems, and oral language development. We acknowledge that no financial interest or benefit has arisen from the direct applications of the research presented in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
(64 reference statements)
1
10
0
1
Order By: Relevance
“…Similarly, in a large sample of almost 1500 monolingual English-speaking children from Australia (Eadie et al 2015), the prevalence of speech sound disorders was partially predicted by SES and maternal education, and children whose mothers had a college or postgraduate degree were half as likely to have a speech sound disorder compared to children whose mothers had completed less than 12 years of schooling. Montanari et al (2020) further found that children of more educated mothers had higher English consonant accuracy than children of less educated mothers at age 3;6. However, the English speech sound production abilities of both groups of children were no longer different one year later after one year of exposure to English in the preschool setting, and maternal education was not related to children's Spanish phonological accuracy at either age.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…Similarly, in a large sample of almost 1500 monolingual English-speaking children from Australia (Eadie et al 2015), the prevalence of speech sound disorders was partially predicted by SES and maternal education, and children whose mothers had a college or postgraduate degree were half as likely to have a speech sound disorder compared to children whose mothers had completed less than 12 years of schooling. Montanari et al (2020) further found that children of more educated mothers had higher English consonant accuracy than children of less educated mothers at age 3;6. However, the English speech sound production abilities of both groups of children were no longer different one year later after one year of exposure to English in the preschool setting, and maternal education was not related to children's Spanish phonological accuracy at either age.…”
Section: Introductionmentioning
confidence: 86%
“…By controlling the language in which mothers received their education, Hoff et al (2018) found that maternal school attainment in English was significantly related to children's English but not to Spanish vocabulary between 30 and 60 months, and maternal level of education in Spanish predicted children's Spanish but not English lexical skills between the same ages. In contrast, all mothers in Montanari et al (2020) were educated in Spanish in Mexico, and therefore, the language in which the mothers had received their education did not explain the differences in English speech and language outcomes between children of more and less educated mothers. Montanari et al (2020) speculated that characteristics other than the language of mothers' schooling may mediate the relationship between general maternal education and children's English abilities.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations